Chemoenzymatic labeling of DNA methylation patterns for single-molecule epigenetic mapping. Issue 16 (3rd June 2022) - Gabrieli, Tslil; Michaeli, Yael; Avraham, Sigal; Torchinsky, Dmitry; Margalit, Sapir; Schütz, Leonie; Juhasz, Matyas; Coruh, Ceyda; Arbib, Nissim; Zhou, Zhaohui Sunny; Law, Julie A; Weinhold, Elmar; et al.
Abstract: DNA methylation, specifically, methylation of cytosine (C) nucleotides at the 5-carbon position (5-mC), is the most studied and significant epigenetic modification. Here we developed a chemoenzymatic procedure to fluorescently label non-methylated cytosines in CpG context, allowing epigenetic profiling of single DNA molecules spanning hundreds of thousands of base pairs. We used a CpG methyltransferase with a synthetic S- adenosyl-l -methionine cofactor analog to transfer an azide to cytosines instead of the natural methyl group. A fluorophore was then clicked onto the DNA, reporting on the amount and position of non-methylated CpGs. We found that labeling efficiency was increased up to 2-fold by the addition of a nucleosidase, presumably by degrading the inactive by-product of the cofactor after labeling, preventing its inhibitory effect. We used the method to determine the decline in global DNA methylation in a chronic lymphocytic leukemia patient and then performed whole-genome methylation mapping of the model plant Arabidopsis thaliana . Our genome maps show high concordance with published bisulfite sequencing methylation maps. Although mapping resolution is limited by optical detection to 500–1000 bp, the labeled DNA molecules produced by this approach are hundreds of thousands of base pairs long, allowing access to long repetitive and structurally variable genomic regions.